Targeted Analysis Reveals an Important Role of JAK-STAT-SOCS Genes for Milk Production Traits in Australian Dairy Cattle - Arun, Sondur J.; Thomson, Peter C.; Sheehy, Paul A.; Khatkar, Mehar S.; Raadsma, Herman W.; Williamson, Peter (Frontiers in Genetics, 2015)
The Janus kinase and signal transducer and activator of transcription (JAK-STAT) pathway genes along with suppressors of cytokine signalling (SOCS) family genes play a crucial role in controlling cytokine signals in the mammary gland and thus mammary gland development. Mammary gene expression studies showed differential expression patterns for all the JAK-STAT pathway genes. Gene expression studies using qRT-PCR revealed differential expression of SOCS2, SOCS4 and SOCS5 genes across the lactation cycle in dairy cows. Using genotypes from 1,546 Australian Holstein- Friesian bulls, a statistical model based on SNPs within 500kb of JAK-STAT pathway genes, and SOCS genes alone was carried out. The analysis suggested that these genes and pathways make a significant contribution to the Australian milk production traits. Selection of 24 SNPs close to SOCS1, SOCS3, SOCS5, SOCS7 and CISH genes were significantly associated with, Australian Profit Ranking (APR), Australian Selection Index (ASI) and protein yield (PY). This study supports the view that there may be some merit in choosing SNPs around functionally relevant genes for the selection and genetic improvement schemes for dairy production traits.